Multifaceted COVID-19-Related Stressors and Associations with Indices of Mental Health, Well-being, and Substance Use Among Young Adults. - Graupensperger, Scott; Cadigan, Jennifer M.; Einberger, Clare; Lee, Christine M. (International Journal of Mental Health & Addiction, 2023)
Alongside direct health concerns pertaining to the SARS-CoV-2 virus, the stressors and life disruptions associated with the COVID-19 pandemic may provoke secondary concerns for health and well-being. The implications of COVID-19-related stressors may be particularly salient for young adults, who are at higher-risk for mental health concerns and substance use behaviors. We developed a multifaceted scale that assessed distinct domains of COVID-19-related stressors and examined associations between these stressors and indices of mental health, well-being, and substance use (alcohol and marijuana use). In April—June of 2020, 1181 young adults were recruited from two- and four-year colleges to participate in this study (M = 20.40; 59.95% women). Exploratory factor analysis identified five domains of COVID-19-related stressors: job insecurity, social/relational, financial, illness-related, and school-related. The overall pattern of results indicated that COVID-19-related stressors were related to poorer mental health and well-being. Social/relational stressors emerged as a primary concern most strongly associated with indices of mental health and alcohol use, relative to other stressors. However, illness-related stressors and school-related stressors were associated with less alcohol use. Stressors associated with the COVID-19 pandemic may impact young adults' health and well-being but disentangling various stressor domains informs more tailored intervention and prevention strategies.